2011
DOI: 10.1007/s00213-011-2192-9
|View full text |Cite
|
Sign up to set email alerts
|

The MEK inhibitor SL327 blocks acquisition but not expression of lithium-induced conditioned place aversion: a behavioral and immunohistochemical study

Abstract: These results indicate that pERK is critical for acquisition, but not expression, of lithium-induced CPA and that its activation in the dorsal striatum, during expression, is not critical for retrieval of the aversive memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 55 publications
(87 reference statements)
2
12
2
Order By: Relevance
“…This effect could not be attributed to US or CS on their own. In particular, failure of US to elicit pERK expression in the PFCx is in agreement with previous studies showing that systemic lithium administration fails to affect ERK phosphorylation in mouse PFCx (Longoni et al, 2011); furthermore, the present results also indicate that sucrose consumption fails to affect ERK phosphorylation in PFCx (Figure 3) when measured 30 min after CS + exposure, overall suggesting that increased ERK phosphorylation in PFCx accompanies the learning of the CS-US association. This conclusion appears in agreement with the observation that CTA acquisition was also accompanied by increased phosphorylation of NR1 receptor subunit in the same area.…”
Section: Discussionsupporting
confidence: 93%
“…This effect could not be attributed to US or CS on their own. In particular, failure of US to elicit pERK expression in the PFCx is in agreement with previous studies showing that systemic lithium administration fails to affect ERK phosphorylation in mouse PFCx (Longoni et al, 2011); furthermore, the present results also indicate that sucrose consumption fails to affect ERK phosphorylation in PFCx (Figure 3) when measured 30 min after CS + exposure, overall suggesting that increased ERK phosphorylation in PFCx accompanies the learning of the CS-US association. This conclusion appears in agreement with the observation that CTA acquisition was also accompanied by increased phosphorylation of NR1 receptor subunit in the same area.…”
Section: Discussionsupporting
confidence: 93%
“…We have found that p-ERK is significantly upregulated immediately after morphine-induced CPP testing task whereas no change is found in rats without performing the task, suggesting that the drug craving may activate the ERK signal pathway. This observation was discrepant with a recent study which suggests that p-ERK is not critical for expression of lithiuminduced conditioned place aversion (Longoni et al 2011). The discrepancy may be due to the difference in the paradigm models.…”
Section: Discussionmentioning
confidence: 72%
“…As such, the affective properties of DREADD‐mediated DVC astrocyte activation remain unclear. A longer protocol may have revealed an effect since three or four conditioning sessions with LiCl does induce CPA in mice (Le Merrer et al, ; Longoni, Spina, Vinci, & Acquas, ; Sanjakdar et al, ; Zhang et al, ). We did, however, find that LiCl injection reduced locomotion during the conditioning trial while CNO treatment did not.…”
Section: Discussionmentioning
confidence: 99%